Co‐created in vivo pharmacology practical classes using the novel organism Lumbriculus variegatus - Julanta J. Carriere; Nia A. Davies; Margaret R. Cunningham; Melisa J. Wallace; Aidan Seeley (Wiley, 2023)
Abstract Co‐creation within higher education emphasizes learner empowerment to promote collaboration between the students and staff, enabling students to become active participants in their learning process and the construction of resources with academic staff. Concurrently, a diminishing number of higher education institutions offer in vivo practical classes, resulting in an in vivo skills shortage. To address this, and to actively engage students in their own learning, we describe the co‐creation of a student‐led drug trial using Lumbriculus variegatus. Under blinded conditions, final‐year undergraduate biomedical science students, under the tutelage of academic staff and fellow students, were involved in the co‐creation of an in vivo practical class to determine the effects of histamine and histamine receptor inverse agonists mepyramine and loratadine. Throughout this process, undergraduate‐ and masters‐level students played key roles in every aspect of practical delivery and data analysis. Herein, students demonstrated the test compounds, both in isolation and in combination, resulted in reduced stereotypical movements of L. variegatus (p < .05, n ≥ 6). 15% of students in the class responded to a feedback survey (n = 8) after the class. Students reported the class provided "real life" insights into in vivo research and enabled the development of hands‐on skills which would be useful in applying in their future careers. All students reported that they enjoyed the class with 25% (n = 2) reporting concerns about animal use in research, enabling useful discussions about animals in research. Moreover, these student‐led in vivo trials add to the pharmacological knowledge of L. variegatus promoting education‐led research.